IMPLEMENTATION OF CLUSTER K-MEANS FOR THE EAST JAVA ENVIRONMENTAL HEALTH AREAS GROUPING IN 2017 - Saarah Puspita Dewi; Mahmod Bin Othman (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2020)
An unhealthy environment is a threat that possibly leads to diseases. Consequently, effective environmental monitoring is needed as an effort to improve environmental quality. The basis for implementing the program to determine the fulfilment of environmental health indicators is program targets. Achievements will be compared with program targets as program evaluations to determine the distribution priority areas for improving environmental health indicators. In order to illustrate the coverage of environmental health services by each district or city in East Java Province, K-Means cluster analysis was administered. The objective of cluster analysis application is to determine the regional distribution status based on the environmental health indicators’ achievement in East Java in 2017. This type of research is a descriptive study using non-reactive methods. The data collected was secondary data based on indicators on the Environmental Health Program in 2017. The results of this study illustrated the distribution of environmental health areas in East Java, there are 3 clusters including cluster 1 (high strata) covering 17 districts or cities, where several environmental health indicators had fulfilled the target, cluster 2 (middle strata) covers 16 districts or cities where several environmental health indicators were almost reaching the target. Finally, cluster 3 (lower strata) covers 5 districts, where several environmental health indicators had not been achieved yet. In conclusion, the Environmental Health Program in 2017 at East Java Province was considered quite successful.